Misorientation dependent thermal condition-solute field cooperative effect on competitive grain growth in the converging case during directional solidification of a nickel-base superalloy. (10th January 2022) - Meng, X.B.; Li, J.G.; Jing, C.N.; Liu, J.D.; Ma, S.Y.; Liang, J.J.; Zhang, C.W.; Wang, M.; Tang, B.T.; Lin, T.; Chen, J.L.; Zhang, X.L.; et al.
Highlights: Thermal condition and solute field are combined to study the competitive grain growth in the converging case. It is the first experimental observation that the grain selection changes from unfavorably oriented grain selection to favorably oriented grain selection as the misorientation of unfavorably oriented grain increases. With the misorientation increasing, competitive grain growth transforms from solute field domination to thermal condition domination. The critical misorientation represents thermal condition and solute field reach equilibrium, and favorably and unfavorably oriented dendrites coexist. Abstract: Nowadays, thermal condition and solute field are considered as the potential dominant factors controlling competitive grain growth during directional solidification process. However, the controlling modes and critical conditions of competitive grain growth have been drastically debated over the past two decades. In this work, thermal condition and solute field are combined to study the competitive grain growth in the converging case by experimental observation and numerical simulation of bicrystal samples. We find the competitive grain growth is controlled by the cooperative effect of thermal condition and solute field, and the controlling modes are related to the bicrystal misorientation between favorably and unfavorably oriented grains. When the unfavorably oriented grain is low misoriented, unfavorably oriented grain dominates grain selection, and the competitive grain growth performs as solute field domination. However, with the increase of unfavorably oriented grain's misorientation, the grain selection converts into favorably oriented grain domination, and the competitive grain growth changes to thermal condition domination. To explain these abnormal transformation phenomena, we propose a misorientation dependent thermal condition-solute field cooperative domination model and identify the critical conditions by a critical misorientation ( θ cm ). According to dynamic equation of dendrite growth, we calculate the critical misorientation θ cm to prove this model. The theoretical calculation results agree well with the experimental results.